Visuals for influence in project management and beyond - van der Hoorn, Bronte (Open textbook library., 2021)
‘Visuals for influence: in project management and beyond’ is a practical guide with 24 visuals to download, adapt and deploy to engage your stakeholders. This practical guide will build your confidence and practical skills to quickly and effectively leverage the benefits of visuals to maximise your influence.